Tularemia‐induced erythema multiforme minor in an 11‐year‐old girl. Issue 4 (26th March 2018) - Coates, Sarah J.; Briggs, Benjamin; Cordoro, Kelly M.
Abstract: Tularemia is a rare and potentially life‐threatening infection caused by the highly infectious gram‐negative coccobacillus Francisella tularensis . We present the case of an 11‐year old girl who presented with erythema multiforme minor in the setting of an indolent but progressive soft tissue infection and was found to have tularemia. We review the role of dermatologists in identifying the features of and complications associated with this rare zoonosis and discuss the potential effect of climate change on its incidence.